Is gold a hedge or a safe haven? An application of ARDL approach - Shakil, Mohammad Hassan (2018)
Purpose – The argument whether gold is a hedge or haven is a debatable Issue. Mainly hedge is a class of asset that is negatively correlated with another asset or portfolio on average. On the other hand a safe haven is an asset or portfolio which is negatively correlated with another asset or portfolio at the time of market turmoil. Therefore the purpose of this research is to take Saudi Arabiaas an example to examine the relationship of gold price in Saudi Arabia with key determinants such as the stock market index oil prices exchange rate interest rate and consumer price index (CPI) by application of the autoregressive distributed lag model (ARDL). Design/methodology/approach – The ARDL analysis was employed by using six variables based on the application of monthly time series data that were collected from 2011 to 2015. Findings – From the present analysis it has been discovered that gold is useful as a portfolio hedge and as a hedge against inflation because it is not affected by the CPI. External factors for example financial crisis may be harmful to the CPI thus adding a certain percentage of gold in the investment portfolio may assist in decreasing the level of risk at the time of financial turmoil. Originality/value – Because gold seems to be a useful portfolio hedge as well as an inflation hedge government policies to curb the import of gold may be futile. The present research suggests that policies that directly address the causes of inflation and provide alternative investment opportunitiesfor retail investors may better serve the objective of decreasing gold imports.